Political Philosophy as a Science for Thomas Hobbes - Shatara, Amer (Jordan Journal of Social Sciences, 2020)
This paper tries to shed light on Thomas Hobbes philosophy, especially his political philosophy or “Science of Politics” as he likes to claim. Science is an important concept in Hobbes philosophy. The aim of constituting such Science, according to Hobbes, is to provide a solution to any conflicts that will lead to war among any society. Consensus, which is the ultimate target in any political science, cannot be attained without the use of clear method. For Hobbes, the best method that produces real science is the geometrical method. In Leviathan and almost in all his books, Hobbes uses this method in order to explain the main political and philosophical issues of the time.To explain something is to show how it come to be, or as he wrote in most of his books,to explain something is to know how it is generated.